A study on the use and function of colour on new branding health club / Muhammad Firdaus Museri - Museri, Muhammad Firdaus (2015)
Colours can make us feel happy or sad, it also can make us feel hungry or relaxed. Colour is ubiquitous in individuals" perceptual experience of the world. Daily encounters with people, objects, and environments are rife ,with colour; colour is even present in dreams. Given the ubiquity of colour in people's lives, it is not surprising that a great deal of research has been conducted over the past century focusing on the physics, physiology, and psychology of colour. Sometimes colours are simply a way of trying to describe the often complex things. Colour is the byproduct of the spectrum of lights, as it is reflected or absorbed, as received by the human brain. Color is the visual perceptual property corresponding in humans to the categories called red, yellow, blue, black, etc. Colour are also relate with our environment, means that, we can see on our living places. From floor to ceiling, paint color reflects your style and makes a personal statement of what home means to us. Color unites one-of-a-kind accent pieces with manufactured items throughout our home.